Increasing Job Satisfaction of Nurses through SBAR Communication in Handover of Nursing Tasks - Yuliyanti, Rina; Arso, Septo Pawelas; Ardani, Muhammad Hasib (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Ineffective communication among nurses poses a risk to patient safety and reduces job satisfaction. Effective communication methods are needed to improve patient safety and nurse job satisfaction. This study aims to determine the effect of the SBAR method implementation at the handover time nurses’ job satisfaction. The study was carried out in Karanganyar Regional Hospital and Soehadi Priyonegoro Regional Hospital, Sragen. The research respondents consisted of nurses at Karanganyar Hospital who were the experimental group and nurses at the Sragen Hospital who were used as the control group, each of which was 32 nurses. The data analysis used the Mann-Whitney and Wilcoxon non-parametric difference test. The results showed that there was no significant difference in job satisfaction between the control group and the experimental group; There is an increase in job satisfaction of nurses after being given the SBAR method treatment. The SBAR method has a significant effect on the increase in job satisfaction of nurses with a value of p = 0.000 (less than 0.05). The SBAR method has an influence on nurses’ job satisfaction. So, this method can be applied in hospitals as a standard communication tool accompanied by training to improve nurses’; skills in using the SBAR communication method.  Abstrak: Komunikasi yang tidak efektif diantara perawat menimbulkan risiko pada keselamatan pasien, serta menurunkan kepuasan kerja. Metode komunikasi yang efektif diperlukan untuk meningkatkan keselamatan pasien dan kepuasan kerja perawat. Penelitian ini bertujuan untuk mengetahui pengaruh pelaksanaan metode SBAR pada saat timbang terima terhadap kepuasan kerja perawat. Studi dilaksanakan di RSUD Kabupaten Karanganyar dan RSUD Soehadi Priyonegoro, Sragen. Responden penelitian terdiri dari perawat RSUD Karanganyar yang menjadi kelompok eksperimen dan perawat RSUD Sragen yang digunakan sebagai kelompok kontrol, masing-masing sebanyak 32 orang perawat. Analisis data menggunakan uji beda non parametrik Mann-Whitney dan Wilcoxon. Hasil penelitian menunjukkan tidak ada perbedaan kepuasan kerja yang signifikan diantara kelompok kontrol dengan kelompok eksperimen; Ada peningkatan kepuasan kerja perawat setelah diberikan perlakuan metode SBAR. Metode SBAR berpengaruh signifikan terhadap peningkatan kepuasan kerja perawat dengan nilai p = 0,000 (kurang dari 0,05). Metode SBAR memiliki pengaruh terhadap kepuasan kerja perawat sehingga metode ini dapat diterapkan di rumah sakit sebagai tool standar komunikasi disertai dengan penyelenggaraan pelatihan untuk meningkatkan keterampilan perawat dalam menggunakan metode komunikasi SBAR.